How can graduate students’ research pressure be transformed into motivation and innovative behavior? The role of graduate students’ mentorship homegate (or team) support - Qiming Li; Xian Du; Hua Chen; Xianli Zhou (Frontiers in Psychology)
IntroductionThis study explores how graduate students’ mentorship homegate (or team) support (GSMTS) and challenging-hindering pressures impact their intrinsic motivation for research, identification with research roles, and innovative behaviors.MethodsData from 548 graduate students were collected using convenience sampling and analyzed using Amos and SPSS statistical software package via questionnaires distributed to universities in SiChuan province of China.ResultThe findings reveal that (1) research stress can not directly and positively predict innovative behaviors among graduate students, while intrinsic research motivation and research role identification mediate the relationship between research stress and graduate students’ innovative behavior; (2) hindering research pressure negatively impacts the intrinsic motivation for research, whereas challenging research pressure has a positive effect; (3) GSMTS directly fosters innovative behaviors among graduate students, with intrinsic motivation and roles’ identification for research as sequential mediators; and (4) GSMTS positively moderates the relationship between challenging research pressure and both the intrinsic motivation for research and role identity.DiscussionThis suggests that higher education institutions should cultivate an optimal research and innovation environment for graduate students by increasing challenging research pressure and reducing hindering pressure. They should also emphasize the development of graduate students’ intrinsic motivation for research and identification with research roles. Concurrently, the role of GSMTS should be highlighted to facilitate both the direct and indirect development of graduate students’ innovative behaviors.